Rapid implant therapies: immediate implant placement and immediate restoration - Yu-Lin Lai; Shou-Yen Kao; Tze-Cheung Yeung; Shyh-Yuan Lee (Elsevier, 2009)
During the last decade, the effectiveness of implant therapy has greatly improved, and the demands of dental esthetics in implant dentistry have become an important issue. The traditional two-stage implant protocol with delayed restoration has a treatment duration of 1-2 years, in which patients had to wear a removable appliance and experienced significant discomfort during the recovery period. Nowadays, immediate implant placement into an extraction site followed by immediate restoration of a dental implant can shorten the dental rehabilitation time and preserve patients' esthetic appearance at all stages of treatment. However, these treatment protocols always pose a great challenge to clinicians, especially when treating patients with preexisting soft and hard tissue deficiencies. The aim of this report is to present various treatment modalities to provide immediate tissue reconstruction and implant restoration following tooth extraction. With appropriate patient selection and careful clinical planning, these treatment strategies can lessen the number of surgeries required, condense treatment times, reduce discomfort to the patient, and accelerate the restoration process.